2022
DOI: 10.1038/s41467-022-34367-6
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated cortical thickness alterations across six neurodevelopmental and psychiatric disorders

Abstract: Neuropsychiatric disorders are increasingly conceptualized as overlapping spectra sharing multi-level neurobiological alterations. However, whether transdiagnostic cortical alterations covary in a biologically meaningful way is currently unknown. Here, we studied co-alteration networks across six neurodevelopmental and psychiatric disorders, reflecting pathological structural covariance. In 12,024 patients and 18,969 controls from the ENIGMA consortium, we observed that co-alteration patterns followed normativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 107 publications
(214 reference statements)
5
52
0
Order By: Relevance
“…We found that betweennetwork RSFC loadings related to the p factor followed the sensory-to-transmodal gradient, with the default and control networks yielding higher between-network FC (i.e., greater integration) while sensory systems exhibited lower between-network FC (i.e., greater segregation), suggesting that connectivity between the two anchors of the principal gradient might be affected by the p factor. This finding is in line with recent studies showing that the sensory-to-transmodal axis is impacted across several disorders (Hettwer et al, 2022;Opel et al, 2020;Park et al, 2022a). As the p factor represents a general liability to all common forms of psychopathology, this points towards a disorder-general biomarker of dysconnectivity between lower-order and higher-order systems in the cortical hierarchy (Elliott et al, 2018;Kebets et al, 2019), which might be due to abnormal differentiation between higher-order and lower-order brain networks, possibly due to atypical maturation of higher-order networks.…”
Section: Discussionsupporting
confidence: 93%
“…We found that betweennetwork RSFC loadings related to the p factor followed the sensory-to-transmodal gradient, with the default and control networks yielding higher between-network FC (i.e., greater integration) while sensory systems exhibited lower between-network FC (i.e., greater segregation), suggesting that connectivity between the two anchors of the principal gradient might be affected by the p factor. This finding is in line with recent studies showing that the sensory-to-transmodal axis is impacted across several disorders (Hettwer et al, 2022;Opel et al, 2020;Park et al, 2022a). As the p factor represents a general liability to all common forms of psychopathology, this points towards a disorder-general biomarker of dysconnectivity between lower-order and higher-order systems in the cortical hierarchy (Elliott et al, 2018;Kebets et al, 2019), which might be due to abnormal differentiation between higher-order and lower-order brain networks, possibly due to atypical maturation of higher-order networks.…”
Section: Discussionsupporting
confidence: 93%
“…Combining connectivity modes has also been used to better resolve clusters of functional activation in BOLD data [84], and inform the application of deep brain stimulation to psychiatric and neurological diseases [11, 67]. Encouragingly, previous work has found that incorporating multiple perspectives of brain connectivity can result in novel discoveries, including improved generative models of brain connectivity [100], structure-function coupling [56, 105], epicentres of transdiagnostic alterations [57, 60], and the characterization of homophilic wiring principles [16].…”
Section: Discussionmentioning
confidence: 99%
“…This approach is already widely used on the haemodynamic BOLD signal but also exists for time-series measures from other imaging modalities such as magneto-/electroencephalography (MEG/EEG) and dynamic FDG-fPET (all called “functional connectivity”) [24, 32, 46, 52, 70]. In cases where multiple measures of a feature exist at each brain region, such as gene expression levels across many genes, connectivity can represent the similarity of brain regions with respect to a single local feature [56, 57, 60, 103, 111, 122, 125]. In each case, the ensuing region × region network represents a form of connectivity between brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…The MRI data was processed using the same analysis pipeline as described above for HBN. Clinical variables included 129 symptom scores decomposed into 7 components using ICA, as reported previously ( Alnaes et al, 2018 ): Attention/ADHD, anxiety, conduct disorder, depression, psychosis prodrome, mania, and obsessive-compulsive disorder ( Hettwer et al, 2022 ). These clinical symptom components reflect increased presence of symptoms.…”
Section: Methodsmentioning
confidence: 99%